Sentence Analysis in CNN Online News Edition 23-29 April 2024 - Seftiani, Helmi; Dinata, Sigit Prasetya; Isya, Muhammad (International Journal of Science and Applied Science: Conference Series, 2023)
Written language contains words, phrases, sentences, clauses, and morphemes. Syntax is a study of word combinations or grammar that studies the combination of words that become sentences, clauses, and phrases and the placement of suprasegmental morphemes according to semantic structure and adjusted to the speaker. The methodology of this study adopts a qualitative approach. Data sources can be documents, surveys, direct observations, interviews, experiments, or other sources used to collect information relevant to specific research or analysis objectives. The data sources that researchers obtain come from the CNN Indonesia website and supporting data sources such as journals and books. The subjects used in this study are objects (laptops, cellphones, which can make it easier for researchers to access the CNN Indonesia website). The data collection technique used is documentation obtained from the CNN Indonesia website.